Estratégias de utilização de Beauveria bassiana (Hypocreales: Cordycipitaceae) visando ao controle de Gyropsylla spegazziniana (Lizer & Trelles, 1919) (Hemiptera: Aphalaridae) - Loeblein, Jaqueline Suelen (2019)
Gyropsylla spegazziniana is considered one of the main pests of yerba mate crop, presenting bioecological aspects that result in losses that have been estimated up to 54%. During its development in the plant, damage during the nymphal phase results in reduced leaf area, increased number of insect particles in the raw material and reduced quality of the final product. Currently, the control is limited to manual collection, pruning and destruction of the infested branches, being prohibited the use of chemical insecticides because it is a product consumed practically “in natura”. Due to the absence of registered chemicals for the control of this insect, it is necessary to explore more sustainable methods that may be used to control this pest. Thus, this study aimed to evaluate strategies for the use of the fungus Beauveria bassiana isolated Unioeste 44, aiming at the management of G. spegazziniana through aqueous spraying with adjuvants and attraction-and-infection devices. The efficacy of the adjuvants with the fungus varied with the inoculation method used, being direct and residual contact. Direct spraying resulted in the highest mortality, ranging from 43-57% for isolated application of Assist® and Áureo® products and 65-74% for application with fungus, while the effect of residual contact resulted in reduced mortality, 6-31%. for application of adjuvants only and 16-48% for application with B. bassiana. Compatibility analysis indicated that the adjuvants evaluated were compatible with the B. bassiana fungus. Four autoinoculation devices were compared under laboratory conditions using different preparations of B. bassiana and diatomaceous earth. Preliminary tests proved the potential for attracting the yellow color of G. spegazziniana to adults, as well as the contamination of insects with surface impregnated with the pathogen. Confirmation of death by the fungus was significant only in the Colortrap® commercially manufactured trap device. Horizontal transmission of fungal infection was observed with both sporulated and living contaminated corpses. Using attraction-and-infection devices, up to 94% of insect mortality in the absence of SPLAT® and 90% in the presence of wax were found, with no increase in mortality when the emulsified SPLAT® wax was used. Pathogen viability was reduced in traps as a function of storage time, but mortality of G. spegazziniana exposed to the fungus remained above 50%, even after 21 days of storage. Bioassays with screened cages showed mortality of 88% of the population. These results indicate that the fungus Beauveria bassiana is promising for use in the control of G. spegazziniana, as well as for the continuity of studies under semi-field and field conditions.